Edukasi dan Pendampingan Digitalisasi Organisasi melalui Implementasi Sistem Informasi di IPSI Cibarusah - Abdul Halim Anshor (DPPM Universitas Pelita Bangsa, 2026)
heavily on manual recording. This condition exists for the IPSI Cibarusah community service team partner, where IPSI administrators face difficulties in managing membership data, training schedules, athlete achievements, and activity documentation due to the lack of an integrated system. This condition indicates two main problems faced by partners: delays and lack of management in recording organizational activities and slow access to information related to organizational activities. The purpose of this community service activity is to provide intensive assistance to IPSI Cibarusah administrators in the process of implementing an information system, as a form of initial digitalization activities in the IPSI Cibarusah organization. The assistance activities are carried out in stages and adjusted to the conditions of the partners, starting with discussions on administrative needs, introducing the concept of system-based data management, to the use of simple web applications in daily administrative activities. This approach was chosen so that administrators can understand the system's functions without abandoning their usual work patterns. During the implementation of the activity, administrators began to become accustomed to recording and managing data through the prepared system. This experience has helped the management reorganize the organization's administration in a more streamlined and centralized manner, while also fostering an understanding of the role of information technology in supporting organizational management. The mentoring provided has demonstrated that the digitalization process can be well-received when tailored to the needs and readiness of partners.